Dampak Kenaikan Harga Barang Pokok terhadap Pola Pengeluaran Masyarakat : Kajian Literatur Ekonomi Konvensional - Rio Dwi Maulana; Reni Ria Armayani Hasibuan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study examines the impact of rising commodity prices on household expenditure patterns from the perspective of conventional economic literature. The review method is used to trace and synthesize the findings of studies published nationally in the last five years. The main objective is to analyze how inflationary pressures on basic necessities such as food, fuel, and housing affect expenditure shifts. The review reveals that rising prices of basic products cause families to reduce discretionary spending, allocate budgets, and occupy lower welfare levels. This study contributes to policy recommendations by identifying the most important expenditure factors and recommending targeted social protection. This conceptual article promotes the role of fiscal and monetary stability in fostering household purchasing power in developing countries such as Indonesia. The impact on the economic bottom line is considered in great depth, strengthening the role of price controls, subsidies, and income redistribution activities..